Lascaux et la conservation en milieu souterrain Actes du symposium internationnal Paris, 26 et 27 Février 2009 - Coye, Noël (Documents d'archéologie française, 2009)
Organized through the initiative of the Ministry of Culture and Communication, the symposium "Lascaux and Preservation Issues in Subterranean Environments" was held in Paris on February 26 and 27, 2009 under the chairmanship of Jean Clottes. It brought together nearly three hundred participants from seventeen countries with the goal of confronting research and interventions conducted in Lascaux Cave since 2001 with the experiences gained in other countries in the domain of preservation in subterranean environments. Twelve presentations addressed questions related to disciplines such as hydrogeology, climatology and microbiology in relation to the protection and valorization of decorated caves. The talks were followed by debates allowing the experts and all other participants to freely express themselves. This volume, which constitutes the proceedings of this symposium, is composed of the studies presented during the sessions and full transcriptions of the debates. It provides both a synthesis of the conservation activities realized at Lascaux between 2001 and 2009 and the state of research and the conditions of the cave as of 2009.